Osteoid osteomas around the ankle managed with cost-effective and clinically efficient percutaneous drilling resection: a case report of two cases in the talus and distal tibial epiphysis - Sonkusale, Aashay; Nagda, Taral; Dhamele, Jaideep; Chaubey, Aditya; Vishwakarma, Praveen; Tandon, Neharika (International Journal of Research in Orthopaedics, 2025)
Osteoid osteoma (OO) is a benign bone tumour characterised by constant pain which is worse at night and relieved by NSAIDs. On imaging, it is seen as a well demarcated rounded osteolytic lesion with a central nidus. It is rarely seen around the ankle joint, and it is easy to miss on primary plain radiographs, especially in children, leading to mid- or delayed diagnosis which is highlighted in this case report. Conservative management with NSAIDs and immobilisation is usually the first line of management. Upon failure of medical treatment, there are various surgical options ranging from open resection to minimally invasive image guided procedures. We present 2 cases of sub-periosteal OO around the ankle- one in the talus and other one in the distal tibial epiphysis. The first case is of a 17-year-old girl, was initially misdiagnosed on plain radiographs and magnetic resonance imaging (MRI) as right ankle synovitis elsewhere and treated with open synovectomy and debridement. She presented to us 4 months after the procedure with incessant right ankle pain not allowing her to perform her routine activities. The second case describes OO in the distal tibial epiphysis of the left ankle in a 12-year-old male child presenting with typical left hind foot pain. We managed both the OO with percutaneous drilling resection (PDR) under computed tomography (CT) guidance with complete resolution of symptoms and full weight bearing within 48 hours. A six-month follow-up reported birth children back to schooling and routine activities with a completely pain free ankle joint. OO around the ankle requires a high index of suspicion. Early diagnosis is often obscured by vague symptoms and complex anatomical location around the ankle. CT scan is considered to be the gold standard; effusion and peri-lesional edema masks the lesion on MRIs. PDR is a cost effective and easy surgical option producing consistent results with low rates of recurrences.